Cedarburg Bog -A National Natural Landmark - (:unkn) unknown (My University, 1974)
The Cedarburg Bog and adjoining upland beech woods were designated, with nine other Wisconsin locations, as National Natural Landmarks. The other sites are the Wyalusing Hardwood Forest in Grant County, Summerton Bog in Marquette County, the Kakagon Sloughs in Ashland County, Abraham's Woods in Green County, Spruce Lake Bog in Fond du Lac County, the Flambeau River Hardwood Forest in Sawyer County, the Finnerud Pine Forest in Oneida County, the Chippewa River Bottoms in Buffalo County and the Chiwaukee Prairie in Kenosha County. Previously, the Ridges Sanctuary in Door County was the only Wisconsin site included.
Keywords: Cedarburg Bog; National Natural Landmark